About the some conditions of the replaceability of the double induction - Maliaukienė, Livija (Lietuvos matematikos rinkinys, 2008)
The provability of the axiom of double induction (ADI) with the open induction formula in the additive arithmetic is investigated. The system of additional axioms and theirs provability by ADI is presented.
Keywords: sequential variant of the first order predicate calculus; additive arithmetic; the provability of the axiom of double induction